2021
DOI: 10.3390/e23091138
|View full text |Cite
|
Sign up to set email alerts
|

TOLOMEO, a Novel Machine Learning Algorithm to Measure Information and Order in Correlated Networks and Predict Their State

Abstract: We present ToloMEo (TOpoLogical netwOrk Maximum Entropy Optimization), a program implemented in C and Python that exploits a maximum entropy algorithm to evaluate network topological information. ToloMEo can study any system defined on a connected network where nodes can assume N discrete values by approximating the system probability distribution with a Pottz Hamiltonian on a graph. The software computes entropy through a thermodynamic integration from the mean-field solution to the final distribution. The na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The results revealed that positions exhibiting correlated changes in both interacting molecules tend to be near the protein–protein interfaces. This observation opened up the possibility of applying statistical inference techniques based on the maximum entropy principle to predict pairs of residues that come into contact solely based on their sequence information and, more specifically, in their evolutionary process.…”
Section: Computational Methods To Predict Protein–protein Interaction...mentioning
confidence: 99%
“…The results revealed that positions exhibiting correlated changes in both interacting molecules tend to be near the protein–protein interfaces. This observation opened up the possibility of applying statistical inference techniques based on the maximum entropy principle to predict pairs of residues that come into contact solely based on their sequence information and, more specifically, in their evolutionary process.…”
Section: Computational Methods To Predict Protein–protein Interaction...mentioning
confidence: 99%
“…The properties of interest for this work are related to entropy and pressure as C normalv = T true( S T true) V α normalv β T = true( P T true) V C normalp = C normalv + V T α normalv true( P T true) V where β T is the isothermal compressibility (the inverse of the bulk modulus), and α v is the volumetric expansion coefficient, shown in Figure . Thanks to correlated sampling, , we can slightly vary the temperature at a fixed volume without the need for any new DFT calculation, obtaining the free energy and its derivatives (the entropy S and the pressure P ) at temperatures surrounding the simulated one. We estimate the thermodynamic relations in eqs – by employing a finite-difference approach on the correlated sampling simulations (see the SI for more details).…”
Section: Methodsmentioning
confidence: 99%
“…The properties of interest for this work are related to entropy and pressure as where β T is the isothermal compressibility (the inverse of the bulk modulus), and α v is the volumetric expansion coefficient, shown in Figure 3 . Thanks to correlated sampling, 19 , 33 35 we can slightly vary the temperature at a fixed volume without the need for any new DFT calculation, obtaining the free energy and its derivatives (the entropy S and the pressure P ) at temperatures surrounding the simulated one. We estimate the thermodynamic relations in eqs 2 – 4 by employing a finite-difference approach on the correlated sampling simulations (see the SI for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Colormaps above the plot depict, from left to right, configurations obtained with h = −5, 0, and 5, respectively. (D) Example of an application of a generalized Ising model to the description of the non-equilibrium steady state of a prey-predator model ( Miotto and Monacelli, 2018 ; Miotto and Monacelli, 2021 ). Normalized entropy as a function of the predator motility obtained neglecting interactions (Shannon-Fano) or considering near-neighbor correlations (Max-Ent).…”
Section: Self-organization and Collective Behaviormentioning
confidence: 99%
“…Varying the external field parameter, h instead modifies the magnetization of the system, as one can see from Figure 5C . Besides its relevance for solid state physics, the Ising model is playing a main role in the area of complex systems as the Hamiltonian (i.e., the energy function) that fully characterize the general Ising or Potts model is the maximum entropy solution for the probability distribution of a system for which densities and correlations are measurable ( Miotto and Monacelli, 2021 ).…”
Section: Self-organization and Collective Behaviormentioning
confidence: 99%